2021
DOI: 10.1186/s43163-021-00099-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel anatomical classification of the frontal sinus: can it be useful in clinical approach to frontal sinusitis?

Abstract: Background We aimed to test the clinical relevance of a newly introduced anatomical classification system of the frontal sinus and to investigate the relation between the frontal sinus type according to this system and the development of frontal sinusitis. We retrospectively evaluated the computed tomography images of 808 frontal sinuses of 404 patients and classified the sinuses as small, medium-sized, and large, based on their size and relation to the orbital roof. We related this classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“… 10 Similar to previous studies, in the present study, the medium-sized category of frontal sinus was the most common type of frontal sinus morphology. 10 , 12 , 22 The values of medium-sized frontal sinus frequency observed in the present study are comparable with the frequency of 65.84% reported in a recent study by Ozdemir et al 22 In contrast, in a study by Yüksel Aslier et al , hyperplasia (44.5%) was the most common type, followed by medium-sized (37.2%), hypoplasia (14.2%) and aplasia (4.1%) categories. 11 Similarly, in a study by Buller et al , following Guerram et al ’s morphologic classification, hyperplasia was found to be the most frequent sinus category (66%), followed by medium-sized (30.2%) and hypoplasia (3.8%) categories.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 10 Similar to previous studies, in the present study, the medium-sized category of frontal sinus was the most common type of frontal sinus morphology. 10 , 12 , 22 The values of medium-sized frontal sinus frequency observed in the present study are comparable with the frequency of 65.84% reported in a recent study by Ozdemir et al 22 In contrast, in a study by Yüksel Aslier et al , hyperplasia (44.5%) was the most common type, followed by medium-sized (37.2%), hypoplasia (14.2%) and aplasia (4.1%) categories. 11 Similarly, in a study by Buller et al , following Guerram et al ’s morphologic classification, hyperplasia was found to be the most frequent sinus category (66%), followed by medium-sized (30.2%) and hypoplasia (3.8%) categories.…”
Section: Discussionsupporting
confidence: 89%
“…[16][17][18][19][20] recent study reported a significant association between the frontal sinus type and frontal sinusitis frequency. 22 In the same study, the prevalence of sinusitis in mediumsized and large sinuses was significantly higher than in small sinuses. 22 Hence, the baseline data of frontal sinus types reported in the present study is helpful in the diagnostic evaluation of sinusitis in the clinical setting.…”
Section: Discussionmentioning
confidence: 75%
“…10 Similar to previous studies, in the present study, the mediumsized category of frontal sinus was the most common type of frontal sinus morphology. 10,12,22 The values of mediumsized frontal sinus frequency observed in the present study are comparable with the frequency of 65.84% reported in a recent study by Ozdemir et al 22 In contrast, in a study by Yüksel Aslier et al, hyperplasia (44.5%) was the most common type, followed by medium-sized (37.2%), hypoplasia (14.2%) and aplasia (4.1%) categories. 11 Similarly, in a study by Buller et al, following Guerram et al's morphologic classification, hyperplasia was found to be the most frequent sinus category (66%), followed by medium-sized (30.2%) and hypoplasia (3.8%) categories.…”
Section: Discussionsupporting
confidence: 88%
“…[16][17][18][19][20] Another recent study reported a significant association between the frontal sinus type and frontal sinusitis frequency. 22 In the same study, the prevalence of sinusitis in mediumsized and large sinuses was significantly higher than in small sinuses. 22 Hence, the baseline data of frontal sinus types reported in the present study is helpful in the diagnostic evaluation of sinusitis in the clinical setting.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation